Graphite as a structural material in conditions of high thermal flux: a survey of existing knowledge and an assessment of current research and development - Kennedy, A. J. (College of Aeronautics, 1959)
The state of fundamental knowledge on the subject of graphite and the graphitisation process is reviewed. The principle methods of manufacture may be considered to include (1) conventional graphitisation of a coke filler-binder mix, (2) the compaction at high pressure and temperatures of natural or artificial graphite particles without a binder, (3) pyrolytic graphites derived from gaseous deposition, and (4) conventional graphites impregnated by liquid or gas and re-graphitised. The present state of development of these processes is examined. The erosion of graphite by high velocity gases at high temperatures is due primarily to oxidation effects which occur preferentially at crystallite boundaries. Coatings of carbides and nitrides improve the resistance at temperatures below about 1700 degrees C, but above this, pyrolytic coatings are more successful. The addition of vapourising compounds, iodides and fluorides, or the addition of carbides and nitrides to the graphite mix, are both beneficial, but of little value at very high temperatures. The development of new graphites, either the impregnated type, or those produced by pressure baking, may offer a margin of improvement, as the best surface structure at temperatures of 3000 degrees C and above appears to be simply graphite. Additions may do little to improve the mechanism of erosion, but they may usefully lower the surface temperature. Considerations relating to thermal shock, creep and fabrication are surveyed. Some of the conclusions are: that graphite is of singular importance to high temperature technology; that commercial issues cannot be allowed to impede vigorous development towards more resistant forms; that much is to be gained by viewing graphite from a metals standpoint; that the fundamental theory of the basic crystal mechanics is undeveloped; that the present wide variability in properties should not be regarded overseriously; that non-destructive assessment by damping measurements needs development, that coatings and impregnants are of high priority, and that, of all factors, oxidation is the most serious limitation to use at the present time.